The complete chloroplast genome of Panicum miliaceum. Issue 1 (1st January 2017) - Cao, Xiaoning; Wang, Junjie; Wang, Haigang; Liu, Sichen; Chen, Ling; Tian, Xiang; Qin, Huibin; Wang, Lun; Na, Xiaofan; Qiao, Zhijun
Abstract: Panicum miliaceum is the most important and ancient domesticated crops in the world. The complete chloroplast genome of P. miliaceum was sequenced using the Illumina Hiseq platform (Illumina Inc., San Diego, CA). The chloroplast genome of P. miliaceum was 139, 929 bp in length, with 38.60% GC content. It contains a pair of inverted repeats (IRs) (22, 723 bp) which were separated by a large single copy (LSC) (81, 918 bp) and a small single copy region (SSC) (12, 565 bp). A total of 132 genes were annotated, which included 84 protein coding genes, 40 tRNA genes and eight rRNA genes. The neighbour-joining (NJ) phylogenetic analysis with the reported chloroplast genomes showed that P. miliaceum chloroplasts are most closely related to those of the Gramineae family.